The Existence Of Customary Institutions In Resolution Of Social Conflict In Indonesian Multicultural Society - Anis Noviya (PT. Anagata Sembagi Education, 2026)
Indonesia is a country with a very high level of ethnic, religious, racial, and inter-group diversity, so that the potential for social conflict is always inherent in the dynamics of everyday social life. Amidst the limited reach, costs, and responsiveness of formal justice institutions, customary institutions continue to exist and play a strategic role as conflict resolution mechanisms based on deliberation, kinship, and local wisdom. This article aims to examine the existence, legal status, and effectiveness of customary institutions in resolving social conflicts in Indonesia's multicultural society, while also identifying the challenges they face in the contemporary era. This research uses a normative juridical method combined with an empirical juridical approach, by analyzing laws and regulations, court decisions, and various literature studies on customary conflict resolution practices in several regions in Indonesia. The results of the study indicate that customary institutions have a strong constitutional basis through Article 18B paragraph (2) of the 1945 Constitution and in practice are able to resolve conflicts more quickly, cheaply, and oriented towards restoring social relations (restorative), compared to formal justice processes that are adversarial in nature. However, the existence of customary institutions still faces challenges in the form of overlapping regulations, weak formal recognition in some regions, and shifting values ​​due to modernization and digitalization. This article recommends strengthening derivative regulations, harmonizing customary law with national law, and revitalizing customary institutions as an integral part of a pluralistic national dispute resolution system